Clinical outcome after rescue intracranial stenting: a comparison of the ACCLINO flex and the CREDO heal stenting platforms after failed mechanical thrombectomy - Christoph M. Mooshage; Niclas Schmitt; Fabian Preisner; Tim Hilgenfeld; Kianush Karimian-Jazi; Michael O. Breckwoldt; Daniel Schwarz; Alexander Hubert; Sophia Hohenstatt; Julius M Kernbach; Alexandra Filipov; Damjan Mirkov; et al. (Neuroradiology, 2026)
Abstract Purpose Mechanical thrombectomy (MT) is the first-line therapy for patients with acute ischemic stroke due to large vessel occlusion; however, despite substantial advances in MT techniques and devices, mechanical recanalization remains unsuccessful in up to 15% of patients. Intracranial rescue stenting represents a promising option to achieve successful recanalization and good clinical outcomes in patients with failed MT. Methods In this retrospective, observational single-center analysis 77 consecutive patients who underwent failed MT and a maximum of 4 unsuccessful device passes were included. The ACCLINO flex stent / CREDO ® heal stent were used in 38 / 39 patients. The study endpoint was a clinically favorable outcome defined as mRS ≤ 3 at 90 days. Results A clinically favorable outcome was achieved in 64.1% (25/39) of patients treated with the CREDO heal stent and in 39.5% (15/38) of patients treated with the ACCLINO flex stents ( p = 0.031). Rescue stenting with the CREDO heal stent (aOR 3.51 95% CI 1.11–11.13, p = 0.033), baseline NIHSS (aOR 0.97 95% CI 0.85–0.97, p = 0.005) and pmRS (aOR 0.52 95% CI 0.31–0.89, p = 0.016) were independently associated with a favorable clinical outcome. Baseline characteristics did not differ between both groups. Conclusions This study suggests that the design of the implanted stent device may influence the clinical outcome. Features such as optimized radial force and thrombogenicity-reducing surfaces of stents used for RIS may improve clinical outcomes of patients treated with intracranial rescue stenting in unsuccessful MT. These findings are hypothesis-generating and require confirmation in prospective, randomized studies.